THE QUESTIONNAIRE OF A PERSONALITY’S FULFILLMENTITY: THE THEORETICAL GROUNDS FOR CREATION AND THE RESULTS OF APPROBATION - Shtepa, Olena (PSYCHOLOGICAL JOURNAL, 2018)
The applied problems of personal self-fulfillment are characterized and the expediency of the term “personality fulfillment” is substantiated. It is theoretically analyzed, that the characterization of self-realization in concepts (pre) certainty led to the identification of this concept with self-realization and its inexpressiveness among the psychological characteristics of the individual. It is substantiated that personality self-fulfillment should be characterized as one of the modes of vital self-realization, which, in relation to professional self-realization, determines the uniqueness of a person’s life path. It is stressed that self-realization is revealed precisely in the existential perspective. The features of the interpretation of personality self-fulfillment in the personalistic and ontological directions of the existential psychology of personality are analyzed. It is theoretically justified that the extreme points of the continuum of personal self-realization are “authenticity - fantasticity”. It is substantiated that psychological resources can be units “making possible” the discreteness of personality self-fulfillment. Personality’s fulfillmentity is characterized as a resource state, which makes it possible for a person to fulfill his own life task in an doing. In the empirical determination of the conservative structure of psychological resources, as well as in the development and approbation of a personality questionnaire of the personality’s fulfillmentity, 542 people aged 18-77 years were involved. The results of regression analysis revealed that, on the whole, 62% of psychological resources are components of personality’s fulfillmentity. The main psychological resources, that characterize both the process and the structure of personality self-fulfillment, are the knowledge of their resources and the ability to invest and update them (is the pointer of psychological resourceful as the ability to operate with their own resources), as well as self-confidence, kindness to people, the pursuit of wisdom , creativity, work on yourself. The results of development and approbation of the author’s questionnaire of personality’s fulfillmentity are given. On the basis of the results of exploratory factor analysis, a two-factor stable structure of personal fulfillment is defined, which as a whole accounts for 88% of the variance. Factor 1 (70%) includes such characteristics of personality’s fulfillmentity, as clearly defined goals and acceptance of the Other, as well as a general indicator of the external form of personality’s fulfillmentity, which characterizes a person’s ability to be understandable to others. Factor 2 (18%) includes such characteristics of personality’s fulfillmentity as productive solitude and responsibility for one’s own choice, as well as an indicator of the internal form of personality’s fulfillmentity that characterizes a person’s ability to be understandable for himself. The characterization of content of personal fulfillment was refined through a description of its correlation with indicators of existential fulfillmentity, self-realization, personal identity, psychological well-being, motivational values, hardiness.